An Introduction to Paleozoic Faunas and Floras of Indonesia - J.T. (Han) van Gorsel (Ikatan Ahli Geologi Indonesia, 2014)
In the Indonesian region the most complete Paleozoic sedimentary section is in West Papua, where parts of the older Australian continental margin sequence are exposed. The oldest fossils are Ordovician-Silurian age corals and graptolites. The only Early Paleozoic fossils in West Indonesia are the enigmatic occurrence of a Devonian coral and stromatoporoid in limestone blocks in a melange section of uncertain age in NE Kalimantan. Late Paleozoic faunas and floras are more widespread across Indonesia, mainly on Sumatra, Timor and West Borneo, where the oldest fossils are of Late Carboniferous and Permian ages.Paleozoic fossils from Indonesia are mainly marine organisms, but non-marine Permian plant fossils are known from Sumatra and West Papua. Some assemblages or species signify 'low-latitude Tethyan' settings; others have 'anti-tropical/subtropical Tethyan' or 'Gondwanan' affinities, which helps constrain plate reconstruction models.